A survey about the contents and features of oncology clinical pharmacy services and self‐evaluations of the oncology pharmacists in China. (26th June 2020) - Wang, Yanting; Dai, Yuanyuan; Yang, Jun; Zhou, Haiyan; Chen, Zhe; Li, Guohui
Abstract: What is known and objective: In China, with the increased number of oncology patients and use of novel antitumour drugs, the demand of oncology clinical pharmacy services is also growing. However, the current status of oncology clinical pharmacy services in China was seldom reported. The purpose of the study was to investigate the contents and features of oncology clinical pharmacy services and self‐evaluations of the oncology pharmacists in China, and to identify related problems for further development. Methods: A 55‐item online questionnaire was distributed to oncology‐related clinical pharmacists in Chinese hospitals in January 2019. Pharmacists answered the questions on the WeChat platform. Data were analysed using descriptive statistics. Results and discussion: The respondents of the 166 valid questionnaires were from 29 provinces (or autonomous regions or municipalities). Their average working experience for clinical pharmacy was 4.86 years. The average duration of their clinical services was 3.27 h/d. The clinical pharmacy services consist of 15 types, and their workload on each service type was summarized. Pharmacists are not frequently participating in establishing pharmacotherapy protocols, therapeutic drug monitoring and pharmacogenetic/pharmacogenomic services. About 80% (81.33%) of the pharmacists thought that other healthcare professionals knew the nature of their work. The biggest barrier for career development of the pharmacists was insufficiency of professional skills. In most cases, the clinical service accounted for <30% of the overall performance evaluation of the pharmacists. Most of the participating pharmacists were not satisfied with their current salary. The overall evaluation score for their career happiness was 6.27 out of 10. What is new and conclusion: The value of oncology clinical pharmacists is being increasingly recognized, but advanced services need further expansion. Increasing the time serving in patient care, optimizing performance evaluation mechanisms and strengthening their skills are possible ways for pharmacists to provide superior services. This study showed the current service of oncology clinical pharmacists in most parts of China, which may provide reference for policymakers, promote international communications and shed light on future development of oncology clinical pharmacy. Abstract : We investigate the contents and features of oncology clinical pharmacy services and self‐evaluations of the oncology pharmacists in China, and to identify related problems for its further development.